Miscodings in Compustat's auditor variable: issues, identification, and correction. (November 2018) - Utke, Steven
Abstract: Using an easily implementable methodology for identifying potential data errors, I identify and correct cases where Compustat miscodes its auditor variable. In this paper, I present the methodology and provide SAS code that implements the methodology, enabling researchers to easily identify and correct auditor variable miscodings. Further, I provide a list of corrections for a sample of Compustat firms from 2001 to 2014. Auditor variable miscodings have implications for both audit-specific research as well as general capital markets research. I find that some of the miscodings arise from the fact that, following an auditor change, the previous auditor's report remains in a firm's 10-K, and Compustat occasionally codes the previous auditor as the current auditor. Aside from identifying and correcting miscodings, I also find that a non-zero number of firms change to a new auditor and then, after only one year with the new auditor, switch back to the prior auditor.